Implementing the MATATAG Curriculum: A Qualitative Study on Teachers’ Challenges, Adaptation Strategies, and Support Needs - Malinao, Ana Joy; Miano, John Joerry (Journal of Interdisciplinary Perspectives, 2025)
Implementing new educational curricula often challenges teachers, requiring them to adapt to new pedagogical approaches, policies, and resource limitations. The MATATAG Curriculum, recently introduced in the Philippine education system, aims to enhance foundational skills and streamline learning competencies. This study explored the challenges, adaptation strategies, and support needs of elementary teachers in implementing the MATATAG Curriculum. Five teachers from particular schools in Santa Cruz Elementary participated in this study. This study used a qualitative, phenomenological research approach and was carried out from December 2024 to March 2025. Focus groups and in-depth interviews were employed as data collection techniques to get answers. The challenges for elementary teachers in implementing the curriculum are Resource and Infrastructure Constraints, Insufficient Training and Professional Development, Adaptability, and administrative work Issues. Themes identified regarding the effects of elementary teachers' challenges implementing the new curriculum include professional identity, mental and emotional stress, and uncertainty about one's capacity to handle stress. Despite these challenges, teachers employed various adaptation strategies such as resource improvisation, peer collaboration, self- directed learning, and time management techniques. However, the study underscores the need for stronger institutional support, including improved resource allocation, more structured training programs, and reduced administrative workload. Addressing these issues will enhance teaching effectiveness, reduce burnout, and ensure a smoother implementation of the MATATAG Curriculum, ultimately improving student learning outcomes.